Analisis kinerja Keuangan dengan Menggunakan Metode Economic Value Added pada Industri Properti - , Bonnie Wahyu Nugroho ([Yogyakarta] : Universitas Gadjah Mada, 2013)
We conducted this study by calculating the EVA on the property sector in Indonesia. With these studies it is expected to help the company to find out their financial performance. The study took six property companies in Indonesia include: PT Lippo Tbk, PT Bakrieland Development Tbk, PT JayaReal Property Tbk, PT Modernland Realty Tbk, PT Summarecon Agung Tbk and PT Duta Pertiwi Tbk. During this decade the development of the property business experienced rapid growth coupled with the improving economic activity back in other words, the activities in the field of property can be used as an indicator of how active the general economic activity is in progress. Development of the property industry needs to be examined carefully, because it can have an impact on two different sides, namely on the one hand, industrial property can be a stimulus for economic activity due to increased activities in the field will drive the increase in property sector activities, and other related sectors. Another sector, excessive development of the property industry can have negative impacts on the economy. Increased industrial properties that are not controlled, so far beyond the requirement may result in disruption of the national economy. The results of the research thesis is to measure the financial performance of property companies in the period 2004 to 2010 carried out an analysis of financial statements for that period and is expected to be used as an additional reference materials and reference for subsequent researchers may provide another alternative to the assessment of company performance and measure the financial health of the company's property.